(untitled) (Bangladesh Journal of Botany, 2025)
The tissues of barley contain high levels of polysaccharides, making most RNA extraction methods unsuitable for handling the excess polysaccharides. The present study compared various RNA extraction methods suitable for extracting RNA from barley leaves at two different growth stages. Intriguingly, found that using an extraction buffer containing guanidium thiocyanate to directly grind barley leaf tissue with 4 µL of 97.4% β-mercaptoethanol produces good-quality RNA from barley leaves at flowering and milky dough stage. Guanidium thiocyanate (GTC) is a RNase activity throughout the extraction process. The high-quality RNA extracted was further used in the downstream process, and the result of RT-PCR clearly showed the expression of the chitinase and β-1,3-glucanase genes. The suggested modifications to the RNA extraction procedure resulted significantly improved RNA quality extracted from the barley leaf tissue. Bangladesh J. Bot. 54(4): 1077-1082, 2025 (December)